(untitled) (Research, Society and Development, 2024)
In the last decade, there was a significant increase in life expectancy in Brazil to an average of 75.5 years, even after the COVID-19 pandemic between the years 2020-2022, and concomitantly with this growth there was also an increase in the number of chronic degenerative diseases. Despite the improvements made in the field of medicine, from the diagnosis to the treatment of these diseases, it became evident the need for a multidimensional instrument to identify in a briefer and more effective way which elderly people are considered frail and have a greater propensity to develop unfavorable outcomes and those who are not. benefit of invasive measures. This article is a descriptive and reflective study structured based on the analysis of articles from different databases published between the years 2019-2023 with the aim of discussing the impact of the 10-minute targeted geriatric assessment (TaGa-10) in predicting the prognosis of elderly patients.